EVANGELISCHE KIRCHE IN DEUTSCHLAND, Pentecostal Movement and Charismatization. Approaches – Suggestions – Perspectives, Leipzig: EKD, 2022, 262 pp., 13 x 20, ISBN 978-33-7407-095-4. (Scripta Theologica, 2023)
Book Review